An Analysis of the Hanyu Pinyin Errors of the Indonesian Students - Ruomei, Fu (Bina Nusantara University, 2013)
Pinyin is a valuable tool for students who learn Chinese as a second language. Through years of teaching practice and observation, some errors in Indonesian studentsâ€™ understanding and using in Pinyin were summed up, includingthe phonetic alphabet equated to the actual voice entirely caused the mispronunciation; lack of understanding in some special provisions in Pinyin caused the confusion of vowels â€œuâ€ and â€œÃ¼â€; improperly placement of tone marks; did not understand the pinyin word-segmentation resulting in memory and understanding of Chinese based on Chinese characters instead of the word as a unit. These errors disturbed the accuracy of Chinese studentsâ€™ pronunciation, caused problems in Chinese vocabulary understanding. It is very important for Indonesian Chinese language learners to lay a solid foundation of Pinyin and develop good habits in the use of Pinyin.